Dynamics of a Predator-Prey Model with Allee Effect and Herd Behavior (Journal of Nonlinear Modeling and Analysis, 2024)
This paper deals with dynamics of a predator-prey model withAllee effect and herd behavior. We first study the stability of non-negativeconstant solutions for such system. We also establish the existence of Hopfbifurcation solutions for such predator-prey model. The stability and bifurcation direction of Hopf bifurcation solution in the case of spatial homogeneityare further discussed. At the same time, several examples are given by MATLAB. Finally, the numerical simulations of the system are carried out throughMATLAB, which intuitively verifies and supplements the theoretical analysisresults.
Keywords: Allee effect; herd behavior; stability analysis; Hopf bifurcation; numerical simulations.